Ground-Air Heat Exchanger as Passive Cooling In Building Ventilation - Ferdi Syaputra S; Remon lapisa; Bulkia Rahim; Rizky Ema Wulansari (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Energy consumption for air conditioning systems and thermal comfort in a building in Indonesia is quite high. The solution that can be developed is to use the thermal inertia stored in the soil. This research aims to design and test the effectiveness of heat transfer between soil-air as a passive coolant in building ventilation systems. This research was conducted for 48 hours, the incoming air velocity was 4.68 m/s, the measurement results showed various weather and temperature conditions including average light intensity of 1822.6 Lux, average ambient temperature of 28.4 °C, average humidity of 99.4%, average room temperature of 30 °C, average water temperature of 28 °C and average soil temperature of 28.1 °C and maximum effectiveness value of 2.46 and minimum air value of 0.9. Experimental results show that groundwater-air heat transfer used as passive cooling in building ventilation systems can provide good performance with temperature reductions reaching 2-10°C. Konsumsi energi untuk sistem pengkondisian udara dan kenyamanan termal bangunan di Indonesia cukup tinggi. Salahsatu solusi yang dikembangkan ialah menggunakan inersia termal yang tersimpan di dalam tanah. Penelitian ini bertujuan untuk merancang-bangun serta menguji efektivitas perpindahan kalor antara tanah-udara sebagai pendingin pasif pada sistem ventilasi bangunan. Penelitian dilakukan selama 48 jam dan kecepatan udara masuk 4,68 m/s, hasil pengukuran menunjukan berbagai kondisi cuaca maupun suhu meliputi intensitas cahaya rata-rata 1822,6 Lux, temperature lingkungan rata-rata 28,4 °C, kelembapan rata-rata 99,4 %, temperature ruangan rata-rata 30 °C, temperatur air rata-rata 28 °C dan temperatur tanah rata-rata 28,1 °C dan nilai efektivitas maksimum sebesar 2,46 dan nilai minimum udara sebesar 0,9. Hasil penelitian menunjukkan bahwa perpindahan kalor air tanah-udara yang digunakan sebagai pendingin pasif pada sistem ventilasi bangunan memiliki kinerja yang cukup baik dengan pengurangan temperatur mencapai 2-10°C.